Determinants of preterm birth among mothers who gave birth in East Africa: systematic review and meta-analysis - Tariku Laelago; Tadele Yohannes; Gulima Tsige (BMC, 2020)
Abstract Background Preterm birth (PTB) can be caused by different factors. The factors can be classified into different categories: socio demographic, obstetric, reproductive health, medical, behavioral and nutritional related. The objective of this review was identifying determinants of PTB among mothers who gave birth in East African countries. Methods We have searched the following electronic bibliographic databases: PubMed, Google scholar, Cochrane library, AJOL (African journal online). Cross sectional, case control and cohort study published in English were included. There was no restriction on publication period. Studies with no abstracts and or full texts, editorials, and qualitative in design were excluded. Funnel plot was used to check publication bias. I-squared statistic was used to check heterogeneity. Pooled analysis was done by using fixed and random effect model. The Joanna Briggs Critical Appraisal Tools for review and meta-analysis was used to check the study quality. Results A total of 58 studies with 134,801 participants were used to identify determinants of PTB. On pooled analysis, PTB was associated with age < 20 years (AOR 1.76, 95% CI: 1.33-2.32), birth interval less than 24 months (AOR 2.03, 95% CI 1.57-2.62), multiple pregnancy (AOR 3.44,95% CI: 3.02-3.91), < 4 antenatal care (ANC) visits (AOR 5.52, 95% CI: 4.32-7.05), and absence of ANC (AOR 5.77, 95% CI: 4.27-7.79). Other determinants of PTB included: Antepartum hemorrhage (APH) (AOR 4.90, 95% CI: 3.48-6.89), pregnancy induced hypertension (PIH) (AOR 3.10, 95% CI: 2.34-4.09), premature rupture of membrane (PROM) (AOR 5.90, 95% CI: 4.39-7.93), history of PTB (AOR 3.45, 95% CI: 2.72-4.38), and history of still birth/abortion (AOR 3.93, 95% CI: 2.70-5.70). Furthermore, Anemia (AOR 4.58, 95% CI: 2.63-7.96), HIV infection (AOR 2.59, 95% CI: 1.84-3.66), urinary tract infection (UTI) (AOR 5.27, 95% CI: 2.98-9.31), presence of vaginal discharge (AOR 5.33, 95% CI: 3.19-8.92), and malaria (AOR 3.08, 95% CI: 2.32-4.10) were significantly associated with PTB. Conclusions There are many determinants of PTB in East Africa. This review could provide policy makers, clinicians, and program officers to design intervention on preventing occurrence of PTB.